ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH DI DESA SIDONDO IV KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Alfad, Alfad; Antara, Made; Damayanti, Lien (AGROTEKBIS, 2017)
The aims of this study is to determine magnitude of farm income and the feasibility of rice plant in at Sidondo IV vilage district of sigi Biromaru. The surveys conducted by the deliberate way (purpossively), the number of farmer respondents in this study was 35 respondents out of 165 farmers who cultivate paddy rice. The analysis used in this study is an analysis of income and feasibility. The analysis showed the average rice production amounted to 1,146.11 kg and the average revenue that farmers have Â Rp. 9,369,828.57/Ha, while the total cost of farmer respondents spend Rp. 3,539,798.57 /0.64 Ha and rice farming income in at Sidondo IV vilage district of Sigi Biromaru Rp. 5,830,030 /0.64 Ha. The analysis indicate Revenue Cost Ratio of paddy rice farming was obtained for 2.64. Accordingly, paddy rice farming in the Sidondo IV village is feasible withÂ  R/C value > 1.Keywords : Feasibility, income, paddy rice farm.